The Effect of Flash Card Media on the Reading Ability of Children Aged 6-7 Years - Evi Setianingsih; Dede Margo Irianto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The aspect of language which is an output support in education services is important to pay attention to in order to initiate the growth and development of children, especially in their reading ability. Based on the background in this study, there are problems related to children's ability to read. This study aims to determine the level of influence of the use of flash card media in solving problems. Data collection techniques in this study were carried out by means of observation and reading performance tests. This research was conducted in two cycles. The object of this research was students of class 1 mars at UPI Laboratory Elementary School. In this study, it was more focused on children who could not read fluently, because the presence of these problems could certainly have an impact on the continuity of the child's learning and development.